Interactive E-LKPD Based on CTL (Contextual Teaching Learning) Assisted Wizer.me to Train Students' Learning Independence in Hydrocarbons - Mahardhika, Sri Renata; Dwiningsih, Kusumawati; Arzety, Tharisth Natasyavira Izza; Nuryanti, Refina; Fathoni, Rizal (Journal of Innovation in Educational and Cultural Research, 2025)
This study aims to design an interactive Electronic Student Worksheet (e-LKPD) based on the Contextual Teaching and Learning (CTL) model, drawing reference from the Wizer.me website, to enhance students' autonomy in learning hydrocarbon materials. Hydrocarbon concepts are abstract and complex, requiring new approaches to learning. Computer-based learning media feature interactive components that support student participation and independence. This research employed the Research and Development (RD) approach utilizing the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The developed e-LKPD was validated with experts at an 88% validity level (very valid). Student response questionnaires yielded a practicality level of 95.83% (very practical), and the student learning independence percentage was 79.42% (practical/effective). The measure of effectiveness, as determined by the n-gain test, was 63.69% (fairly effective). These findings demonstrate that the interactive e-LKPD is a valid, feasible, and effective learning tool to support students' learning independence in hydrocarbon materials. This study contributes to the use of digital learning media in chemistry education, facilitating student-centered learning and active participation.